Aktivitas Antibakteri Lactobacillus plantarum 1 RN9 Terhadap Escherichia coli ATCC 25922 - Denok Wihartati, Lucia; Mayun Permana, I Dewa Gde; Indri Hapsari Arihantana, Ni Made; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
The objectives of this research were to determine the antibacterial activity of Lactobacillus plantarum 1 RN9 on several metabolites with different incubation times against E. coli ATCC 25922 and to determine its optimum incubation times in producing the highest antibacterial activity against Escherichia coli ATCC 25922. This research used L. plantarum 1 RN9 which was isolated from dadih ( Dadih is a typical Minang fermented milk made from buffalo milk, keep 2 nights in a bamboo tube covered with banana leaves), incubation times (12, 24, 36, and 48 hours), with three types of supernatant namely cell-free supernatant (CFS), neutral cell-free supernatant, and heated neutral cell-free supernatant. The supernatants were tested for its antimicrobial activity against E. coli ATCC 25922. There were two methods used in this research, namely agar-based disk diffusion and contact method. The highest antimicrobial activity of L. plantarum 1 RN9 against E. coli ATCC 25922 with cell-free culture supernatant was shown by isolate RN9 at incubation time of 24 hours with a decrease of 1.76 log cycle and 6.50 mm inhibition diameter.